Establishment of a serum IgG4 cut‐off value for the differential diagnosis of IgG4‐related sclerosing cholangitis: A Japanese cohort. Issue 7 (20th June 2013) - Ohara, Hirotaka; Nakazawa, Takahiro; Kawa, Shigeyuki; Kamisawa, Terumi; Shimosegawa, Tooru; Uchida, Kazushige; Hirano, Kenji; Nishino, Takayoshi; Hamano, Hideaki; Kanno, Atsushi; Notohara, Kenji; Hasebe, Osamu; et al.
Abstract: Background and Aim: IgG4‐related sclerosing cholangitis (IgG4‐SC) must be precisely distinguished from primary sclerosing cholangitis and cholangiocarcinoma (CC) because the treatments are completely different. However, the pathological diagnosis of IgG4‐SC is difficult. Therefore, highly specific non‐invasive criteria such as serum IgG4 should be established. This study established a cut‐off for serum IgG4 to differentiate IgG4‐SC from respective controls using serum IgG4 levels measured in Japanese centers. Methods: A total of 344 IgG4‐SC patients were enrolled in this study. As controls, 245, 110, and 149 patients with pancreatic cancer, primary sclerosing cholangitis, and CC, respectively, were enrolled. IgG4‐SC patients were classified into three groups: type 1 (stenosis only in the lower part of the common bile duct), type 2 (stenosis diffusely distributed throughout the intrahepatic and extrahepatic bile ducts), and types 3 and 4 (stenosis in the hilar hepatic region) with 246, 56, and 42 patients, respectively. Serum IgG4 levels were compared, and the cut‐offs were established. Results: The cut‐off obtained from receiver operator characteristic curves showed similar sensitivity and specificity to that of 135 mg/dL when all IgG4‐SC and controls were compared. However, a new cut‐off value was established when subgroups of IgG4‐SC and controls were compared. A cut‐off of 182 mg/dL can increase the specificity to 96.6% (4.7% increase) for distinguishing types 3 and 4 IgG4‐SC from CC. A cut‐off of 207 mg/dL might be useful for completely distinguishing types 3 and 4 IgG4‐SC from all CC. Conclusions: Serum IgG4 is useful for the differential diagnosis of IgG4‐SC and controls.